The impact of volcanic emission of halogenated compounds on the Southern Hemisphere and Antarctic environment - M. Basylevska; V. Bogillo (Ukrainian Antarctic Journal, 2021)
The study aims to estimate and compare the global emission for 20 halocarbons from volcanic and hydrothermal sources into the Earth’s atmosphere. It follows from the results that the contribution of volcanic emission for these species in the depletion of stratospheric ozone in the catalytic halogen cycles does not exceed 0.1%. Still, they significantly impair the level of tropospheric ozone near the volcanoes. The scheme of gas-phase free radical chain halogenation of the hydrocarbons is proposed and confirmed by thermodynamic and kinetic calculations. This explains the experimental ratios between concentrations of CH3I : CH3Br : CH3Cl and CCl4 : CHCl3 : CH2Cl2 : CH3Cl in the volcanic gases. The possible volcanic emission of halocarbons from Erebus and explosive eruptions in the Southern Hemisphere during the Holocene do not have a notable impact on their content in the Antarctic ice. However, volcanic emission of hydrogen halides (HX, X = Cl, Br or I) from powerful eruptions in the Southern Hemisphere during Holocene could deplete the stratospheric ozone substantially, causing a drastic impact of the harmful UV-B radiation on the biota of continents and ocean. We calculated the injected Equivalent Effective Stratospheric Chlorine values and estimated the column ozone percentage change, Δ%O3, for 20 known volcano eruptions in the tropical belt and Southern latitudes. The estimates lead to more than 50% depletion of stratospheric ozone after past powerful volcanic eruptions. The range is estimated for possible ozone depletion after the eruption of Deception Island’s volcano occurred near 4000 BP (from 44 to 56%), which is comparable with those from Krakatoa, Samalas, and Tambora eruptions. A similar analysis was carried out for 192 yrs series of Mt Takahe (West Antarctica) halogen-rich volcanic eruptions at 17,7 kyr, showing extensive stratospheric ozone depletion over Antarctica. Crude estimations of stratospheric ozone depletion (Δ%O3) after Ferrar Large Igneous Province eruptions (183 Ma) in Antarctica were performed, considering the whole LIP volume of basaltic lavas, and they range from 49 to 83%. Given the very low emission rate of HCl due to non-eruptive degassing of the Mt. Erebus volcano, the volcanic emission of Erebus could not be a fundamental reason for modern springtime ozone hole formation over Antarctica.